2008
DOI: 10.1213/ane.0b013e3181875fb0
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Exposure to High or Low Cortisol Has Biphasic Effects on Inflammatory Response Pathways of Human Monocytes

Abstract: BACKGROUND Recent studies demonstrate that glucocorticoids (GCs) have both supportive (stimulatory) and suppressive effects on immune responses, depending upon the GC concentration. Since some GC effects on inflammation are stimulatory, we hypothesized that acute in vivo GC depletion would decrease inflammatory responses of human monocytes. METHODS Monocytes were isolated from healthy volunteer participants before and after in vivo treatment with; 1) IV saline, 2) IV high dose hydrocortisone (8 μg · kg−1 · m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 48 publications
1
21
0
1
Order By: Relevance
“…Relative fluorescence units were assigned to these values and these data were used to generate the expression profiles delineated in the text. Consistent with our previous studies 36,37 , no changes in β-actin expression were observed with cortisol treatment excluding this as a source of bias in the analyses. The expression values of experimental genes were therefore normalized to their respective β-actin values.…”
Section: Methodssupporting
confidence: 90%
“…Relative fluorescence units were assigned to these values and these data were used to generate the expression profiles delineated in the text. Consistent with our previous studies 36,37 , no changes in β-actin expression were observed with cortisol treatment excluding this as a source of bias in the analyses. The expression values of experimental genes were therefore normalized to their respective β-actin values.…”
Section: Methodssupporting
confidence: 90%
“…It has been shown experimentally that even stress concentrations of cortisone can increase CD163 expression, and monocytes with significantly enhanced CD163 have been detected after infusion of endotoxin in healthy persons as well as in patients with severe burn injury. [47][48][49] Therefore, it might be speculated that the stress-inducible Hb scavenger system has developed under the evolutionary pressure of infectious hemolytic diseases such as malaria. In these conditions, activation of the endogenous stress response might support monocyte/macrophage adaptation to extracellular Hb.…”
Section: Discussionmentioning
confidence: 99%
“…GCs have been shown to inhibit the release of pro-inflammatory cytokines including TNF-a, interleukin-1 (IL-1) and interleukin-6 (IL-6) [17], but promote phagocytosis of apoptotic cells by macrophages [30]. In addition, GCs have also been shown to induce changed expression of many pro-and antiinflammatory genes in human monocytes [31,32]. Recently, Li et al [33] reported that dexamethasone decreased the expression of CSE in isolated rat neutrophils.…”
Section: Introductionmentioning
confidence: 99%